Desenvolvimento de um modelo experimental de pânico situacional - Prado, Marinaldo Barbosa (2018)
Although panic attacks are similar to fear, they are not accompanied by activation of the hypothalamus-pituitary-adrenal axis (HPA). The HPA axis remains likewise inactive in experimental panics to electrical stimulations of dorsal periaqueductal gray matter (DPAG). Because glucocorticoids have prominent roles in memory consolidation, the quiescence/inhibition of the HHA axis may protect the individual against the development of situational panic and agoraphobia. Therefore, the present study examined whether the aversive stimulation of MCPD supports the acquisition of conditioned responses to the context and whether these responses are facilitated by restraint stress (10 min) or the corticosterone (10 mg / kg, IP) applied 90 min or immediately before the test session. For this, the rats were subjected to either a subcutaneous shock or a DPAG stimulation and exposed to the respective context 7 days later. Pairings were then repeated for 5 consecutive days. Surprisingly, while shocked rats presented robust freezing responses in all re-exposures, DPAG- estimulated rats showed an expressive increase of activity (conditioned hyperactivity) that was progressively attenuated over 5 exposures. In contrast, neither the freezing nor the hyperactivity was observed during re-exposures to the context of stimulation carried out at 24 h intervals. Remarkably, as well, while hyperactivity was facilitated by a stress contiguous to the re-exposure, it was abolished by the stress performed 90 min before. Corticosterone had effects similar to contingent stress. These results suggest that stress contingent to panic attack favors the development of both situational panic and agoraphobia